The Effect of Physical and Socio-cultural Environments on the Access of Family Planning Service in Poor Couples of Reproductive Age in Sabu Raijua Regency - Paulus, Aysanti Yuliana; Lette, Arman Rifat (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
One strategic decision from Indonesian government in order to slow the rate of population growth is national family planning (FP) program. One common problem regarding contraceptives in the community is the presence of negative perception regarding contraceptives. Numerous growing rumors or believes in the community often produces fear regarding contraceptives usage. This research aimed to analyze and study the influence of physical and socio-cultural environments on the access of family planning service in poor couples of reproductive age in Sabu Raijua Regency. This was an analytic observational study using mixed method. The results of quantitative analysis showed that factors which affect the access of FP service in poor couples of reproductive age were believe (p-value of 0.046), significant others (p-value of 0.014), and transportation (p-value of 0.0001). Meanwhile, tradition did not have significant effect (p-value of 1.000). From the results of qualitative analysis, several believes were found in the people of Sabu Raijua Regency, namely: FP could cause disease, FP could cause infertility, ancestor’s prohibition, and local believes (Jingitiu). Significant others factors consisted of lack of support or the presence of prohibition from husband or parent-in-law on the ground of fear that the wife could be sick or could not work appropriately. Transportation factor consisted of lack of private vehicle or public transportation which made the respondent reluctant to access FP service (probability of 92.99%).